Scale insect species names that have been combined with the genus name Dactylopius Costa (Hemiptera: Sternorrhyncha: Coccomorpha) - Williams, Douglas J.; Ben-Dov, Yair (Zootaxa, 2015)
The genus Dactylopius is the only genus at present in the family Dactylopiidae. Since the name Dactylopius was proposed in 1829, however, numerous other species names belonging to different families of scale insects have been combined with it and these are also listed. The present status and the family placement are also given for each species.